Chromatography-Mass Spectrometry in Modern Physical Research Methods - Khaydarov Gayrat Shoyimovich; Kholmirzaev Mekhroj Murodillayevich; Tilyabov Makhsudjon Umurzkhovich; Abdusoliev Shakzod Sharafiddin o’g’li; Saitkulov Foziljon Ergashevich (Genius Journals, 2023)
Chromatography-mass spectrometry data is analyzed in two ways. According to the first method, the mass spectra recorded at various points of the mass chromatogram are analyzed by comparison with the mass spectra of the standards collected in the database
Keywords: Chromatography; mass spectrometry; first method; various points